Psychometric Properties of the Spanish Clance Impostor Scale (S-CIPS) - Sandoval-Lentisco, Alejandro; Tortajada, Miriam; Palmero, Lucía B.; Campoy, Guillermo; Fuentes, Luis J.; Martinez-Perez, Victor (Anales de Psicología / Annals of Psychology, 2024)
The aim of this study was to examine the reliability, validity, and factorial structure of the Spanish version of the Clance Impostor Phenomenon Scale (CIPS). A sample of 271 Spanish students was recruited to complete a translated version of the original 20-item CIPS. In our sample, the instrument showed high internal consistency reliability (ωTotal =.90) and a moderate-to-strong correlation with measures of depression (r = .633), self-esteem (r = -.754) and fear of negative evaluation (r = .666), suggesting both nomological and discriminant validity. Although the original validation of the CIPS proposed a factorial structure with three factors, subsequent validations also revealed adjustment to two- and one-factor structures. Here, we used confirmatory factor analysis (CFA) to test the three different models. The results showed that in our adaptation, a 2-factor structure might be preferred. This adaptation of the CIPS to Spanish provides clinicians with a new method to gain insight into the psychological mechanisms behind the Impostor phenomenon and suitable treatments.